Therapeutic challenges in a case of psoriasis with nail onset - Mădălina I. Mitran; Cristina I. Mitran; Maria I. Sârbu; Vasile Benea; Mircea Tampa; Simona R. Georgescu (Journal of Mind and Medical Sciences)
Nail psoriasis affects a large number of patients with psoriasis and has a major psychosocial impact. Furthermore, it may be regarded as a predictor of more severe forms of psoriasis and early sign of psoriatic arthritis. The clinical presentations vary depending on the structure affected (nail matrix or nail bed), the nail lesions may range from minor to severe, but they are not specific. Treatment is a challenge, in most cases the lesions being resistant to therapy. We present a rare case of psoriasis with nail onset in a 59-year-old woman. The nail involvement confined to the fingernails was severe, with significant impairment of the patient’s quality of life. Conventional therapies failed to improve the nail lesions, but a marked improvement was achieved under etanercept therapy